2022
DOI: 10.3389/fpubh.2021.751150
|View full text |Cite
|
Sign up to set email alerts
|

Video Calls for Older Adults: A Narrative Review of Experiments Involving Older Adults in Elderly Care Institutions

Abstract: Social isolation in geriatric institutions is a real threat to older adults' (OAs) well-being. Visits from family members, when they are not impacted by geographical distance or illness, sometimes fail to provide sufficient opportunities for social connectedness and interaction to prevent and/or combat OAs' loneliness and social isolation. Information and Communication Technologies (ICTs) offer promising solutions to this problem. Video calls provide a quick and convenient way for remote communication between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…However, the new activities were essentially videocalls, and considering their frequency (> 70%), this practice seems to have been a panacea, that is, a transversal solution that residential care facilities found to fill the gap left by the isolation and a lack of visitation. These results are coherent with the study by Naudé et al ( 2022 ), which shows that many geriatric institutions around the world promoted videocalls due to the pandemic. Although videocalls can provide a solution regarding connection and social contact at a distance (Inzitari et al, 2020 ), they tend to be sporadic and short-lived activities (Naudé et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the new activities were essentially videocalls, and considering their frequency (> 70%), this practice seems to have been a panacea, that is, a transversal solution that residential care facilities found to fill the gap left by the isolation and a lack of visitation. These results are coherent with the study by Naudé et al ( 2022 ), which shows that many geriatric institutions around the world promoted videocalls due to the pandemic. Although videocalls can provide a solution regarding connection and social contact at a distance (Inzitari et al, 2020 ), they tend to be sporadic and short-lived activities (Naudé et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…These results are coherent with the study by Naudé et al ( 2022 ), which shows that many geriatric institutions around the world promoted videocalls due to the pandemic. Although videocalls can provide a solution regarding connection and social contact at a distance (Inzitari et al, 2020 ), they tend to be sporadic and short-lived activities (Naudé et al, 2022 ). Additionally, several technical and human factors can become barriers in the use of videocalls, such as the cognitive and physical capacities required, the complexity of technological devices and the limited digital skills (Naudé et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A mixed-method study among family caregivers of LTC residents living with dementia reported a similar trend, as almost a quarter of responders perceived virtual visits as “ineffective” [ 55 ]. Of note, we highlight a discordance between our qualitative finding on the limited feasibility of virtual visits, and our quantitative survey results that show these visits as the most feasible (86.6%), a finding which is also replicated in the published literature [ 58 ]. This variance could be attributed to retrospective bias, variability of stakeholder groups responding to the survey and interviews, and differences in IT infrastructure and facilitation capacity among LTC homes needed for a successful implementation of virtual visits.…”
Section: Discussionmentioning
confidence: 48%